2018
DOI: 10.1126/sciadv.aap9744
|View full text |Cite
|
Sign up to set email alerts
|

Critical behavior within 20 fs drives the out-of-equilibrium laser-induced magnetic phase transition in nickel

Abstract: High-harmonic spectroscopies reveal that fast energy transfer within 20 fs triggers ultrafast magnetic phase transition in Ni.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
131
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 48 publications
20
131
0
Order By: Relevance
“…As this demagnetization is due to optically induced transitions only, these results may explain the early phase of the demagnetization happening during the pulse through light-induced Stoner excitations. This contribution supplements the others, as, e.g., the ultrafast generation of magnons, whose roles are still heavily debated [19][20][21][22][23][24] in the explanation of ultrafast lightinduced demagnetization. However, unlike other mechanisms where the angular momentum has to be transferred to other baths, such as phonons through Elliott-Yafet scattering [18] or the ultrafast Einstein-de Haas effect [25], these Stoner excitations are directly induced by light and no other dissipation channel is required to allow a spin flip.…”
supporting
confidence: 53%
“…As this demagnetization is due to optically induced transitions only, these results may explain the early phase of the demagnetization happening during the pulse through light-induced Stoner excitations. This contribution supplements the others, as, e.g., the ultrafast generation of magnons, whose roles are still heavily debated [19][20][21][22][23][24] in the explanation of ultrafast lightinduced demagnetization. However, unlike other mechanisms where the angular momentum has to be transferred to other baths, such as phonons through Elliott-Yafet scattering [18] or the ultrafast Einstein-de Haas effect [25], these Stoner excitations are directly induced by light and no other dissipation channel is required to allow a spin flip.…”
supporting
confidence: 53%
“…When we use a π pulse, the correlation function C(l, t) similarly collapses within 20 fs. This nicely explains why experimentally Tengdin et al [34] reported a magnetic phase transition within 20 fs.…”
Section: B Spin-spin Correlation Collapse Within 20 Fssupporting
confidence: 66%
“…Second, we are able to describe these spin waves of wavelength over hundred lattices. Our finding does not only explain the band mirroring effect [33] and ultrafast magnetic phase transition within 20 fs [34], but opens the door to a fresh paradigm for laser-induced ultrafast demagnetization. * guo-ping.zhang@outlook.com…”
Section: Discussionmentioning
confidence: 76%
“…The XUV probe's energy range allows core level to valence transitions to be measured, with the photoexcited change in absorption containing both electronic and structural dynamics 7 . The combination of temporal resolution and probed energy range possible with XUV sources has led to new insights into the first few-femtoseconds of photoexcitation, as well as into the longer timescale dynamics of electron-phonon and phonon-phonon scattering [8][9][10][11][12][13][14] . The same is true for x-ray transient absorption studies performed using x-ray free electron lasers and synchrotrons [15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%